2022
DOI: 10.1177/08948453221100549
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Family Socioeconomic Status, Teacher–Student Interactions, and Career Ambivalence/Adaptability: A Three-Wave Longitudinal Study

Abstract: Using three-wave longitudinal data, this study tested the potential mediating roles of teacher–student relationship quality and teachers’ career support efficacy in the association between Chinese adolescents’ family socioeconomic status (SES) and career development ( N = 1410). Results showed that adolescents’ family SES at Wave 1 was negatively associated with their career ambivalence at Wave 3 via positive associations with both teacher–student relationship quality and teachers’ career support efficacy at W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Results of confirmatory factor analyses for all the constructs to support their construct validity were displayed in Table 1. Also, in previous research, all the currently used scales have demonstrated good reliability and validity in Chinese middle school samples (e.g., Zheng et al, 2022;Zhou et al, 2020).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Results of confirmatory factor analyses for all the constructs to support their construct validity were displayed in Table 1. Also, in previous research, all the currently used scales have demonstrated good reliability and validity in Chinese middle school samples (e.g., Zheng et al, 2022;Zhou et al, 2020).…”
Section: Methodsmentioning
confidence: 91%
“…First, as the developmental inequality in economic and associated resources for career development across different regions of China, parents' expectations may be different due to different (infra)structure and western influences resulted from the globalization (Zheng et al, 2022). Although we have sought to recruit parents from both urban and rural areas and increase the diversity of the sample in terms of regions and educational attainment, the findings need to be replicated using a representative national sample in future and possible region differences may be explored.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores on the closeness subscale represented closer relationships with the teacher, and higher scores on the conflict subscale represented more conflictual relationships with the teacher. The Chinese version of the STRS has been shown to have high internal consistency in previous studies (above 0.8), as well as adequate test–retest reliability and good validity (Guan et al, 2020; Zheng et al, 2023). In the present study, Cronbach's α reliabilities of the closeness and conflict subscales were .90 and .89, respectively.…”
Section: Methodsmentioning
confidence: 91%
“…Teachers are important people for adolescents at school, and their behaviors have an important influence on adolescents’ academic achievement and mental health [ 9 , 10 ]. As a positive factor in the teacher–student interaction, previous studies have confirmed that teacher support not only predicts adolescents’ smartphone addiction and mental well-being [ 11 , 12 ], but also influences their career ambivalence and adaptability [ 13 ]. Indirect research has shown that teacher support helps students create a favorable class atmosphere and establish an amicable teacher–student relationship [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%